Birds as useful indicators of high nature value farmlands : using species distribution models as a tool for monitoring the health of agro-ecosystems - Morelli, Federico (Ecologist); Tryjanowski, Piotr (Springer, 2017)
This book helps to establish a simple framework to identify and use bird species as a bioindicator for high nature value (HNV) farmlands. This book focuses on suitable methods for monitoring the HNV areas, and presents the results of several case studies. The chapters put forward ways to integrate ecosystems assessment, geographical information systems (GIS) and strategies for conservation of local biodiversity. An innovative framework focuses on the use of species distribution models (SDMs) in order to explore the importance of each characteristic of HNV farmlands. Furthermore, the book examines the relationships among bird species richness, land use diversity and landscape metrics at a local scale in the farmlands.
Keywords: Indicators (Biology); Birds -- Ecology.; Farms.; elektronické knihy; electronic books